2018
DOI: 10.1002/bse.2181
|View full text |Cite
|
Sign up to set email alerts
|

How industry peers improve your sustainable development? The role of listed firms in environmental strategies

Abstract: Factors driving firms to become more sustainable have been widely investigated in the literature on environmental strategy, but some important horizontal factors are still missing, such as influence from peers in the same industry. Drawing on signaling theory and expectancy theory, we complement existing studies by highlighting the role of listed firms in raising other firms' awareness and motivation of adopting environmental strategies, while taking the moderating capability factor into account. By setting ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 154 publications
(251 reference statements)
3
69
0
Order By: Relevance
“…Byron and Post () suggested that researchers should look to the institutional contexts in which firms operate to determine specific circumstances where women as board members offer the greatest value. Furthermore, stakeholders' expectations and attitudes toward environmental performance depend on the unique characteristics of certain industries (Bansal & Roth, ; Bowen, ), and industry peer pressure is found to be linked with both reactive and proactive environmental strategies (Yang, Wang, Hu, & Gao, ). Li et al () argued that studying the industry context would provide insight into potential differences that gender diversity at the board level might have based on industry characteristics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Byron and Post () suggested that researchers should look to the institutional contexts in which firms operate to determine specific circumstances where women as board members offer the greatest value. Furthermore, stakeholders' expectations and attitudes toward environmental performance depend on the unique characteristics of certain industries (Bansal & Roth, ; Bowen, ), and industry peer pressure is found to be linked with both reactive and proactive environmental strategies (Yang, Wang, Hu, & Gao, ). Li et al () argued that studying the industry context would provide insight into potential differences that gender diversity at the board level might have based on industry characteristics.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Business sector is a factor that can be associated with the market value of the company (Jia & Zhang, ). The sector in which a company operates could have an effect on the distribution of resources, public exposure, and stakeholder expectations (Jain, Aguilera, & Jamali, ; Siddique & Sciulli, ; Yang, Wang, Hu, & Gao, ). Therefore, firms in specific sectors (e.g., with more visibility, more need to promote good public relations or more social impact) are more likely to develop social practices, whether unilaterally or in response to demand, that inform stakeholders of the firm's social commitment (Aqueveque, Rodrigo, & Duran, ; Gómez‐Bezares, Przychodzen, & Przychodzen, ; Yang et al, ).…”
Section: Literature Review and Study Hypothesesmentioning
confidence: 99%
“…Similar to Yang et al (2018), this study uses the total dollar value of laggard companies' investments in research and development as the proxy of their investments in proactive environmental strategies. Promotion of a sustainable natural environment requires amendments in operating processes (Braungart, McDonough, & Bollinger, 2007).…”
Section: Dependent Variablementioning
confidence: 99%
“…Banerjee (2002) suggests that the environmental orientations of companies determine their strategies. This paper focuses on the latter and contributes evidence of a process that governs investments in proactive environmental strategies, and builds on the evidence of competitive dynamics affecting investments in environmental strategies (González-Benito & González-Benito, 2006;Yang, Wang, Hu, & Gao, 2018). This paper relies on institutional theory and the resource-advantage theory of competition-recognizing that companies compete on environmental issues (Bansal & Roth, 2000)-and on indications that companies are generally business-focused when pursuing environmental actions (Karnani, 2011;Landrum & Ohsowski, 2018).…”
Section: Introductionmentioning
confidence: 99%